Cadaveric Training for Peripheral Neuropathy: Bridging Anatomy, Precision, and Surgical Proficiency - Marcos Daniel Arciniega; Prudhvi Gundupalli; Alexandra Munson; Laszlo Nagy (Anatomia)
Background: Peripheral nerve surgeries require extensive practice to address anatomical variability and effectively manage neuropathy symptoms. While these procedures are increasingly performed by other surgical specialists, neurosurgeons bring unparalleled expertise in the central and peripheral nervous systems. Microscopic surgical techniques are essential for minimally invasive procedures, and cadaver-based education provides an invaluable medium for trainees to practice these techniques. However, few papers address these concepts in tandem. This study explores lesser-known peripheral nerve entrapments, highlights minimally invasive microscopic approaches, and advocates for cadaver-based training. Methods: Willed cadavers were embalmed through approved methods by the state anatomical board. For each decompression procedure, a 1–2 cm keyhole incision was made. Further methods are described in each nerve entrapment surgery below. Exploratory sessions with wider incisions were conducted either before or after the minimally invasive procedure to review anatomy or assess procedural success, respectively. Results: Neurosurgical medical education using cadavers allows trainees to practice techniques and enhance their skillset. Cadavers provide a valuable medium for exploring the relevant anatomy and visualizing the correct procedural steps after minimally invasive surgeries. Using microscopes for the procedures further facilitates detailed anatomical observation and technique refinement. Conclusions: Here, we show that cadaver-based medical education offers a realistic and controlled environment for exploring anatomical variability and refining surgical techniques. This method allows for a visual, mental, and tactile understanding, while performing minimally invasive procedures with a microscope on cadavers further enhances trainees’ proficiency, precision, and confidence, equipping them with the skills needed for improved surgical outcomes.